Zagadnienie modernizacji w pismach wybranych przedstawicieli Ośrodka Myśli Politycznej - Pabich, Marek (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The paper discusses modernisation as viewed by some authors publishing at the Centre of Political Thought. Their reflections focus on a variety of aspects of this issue: efforts to catch up with Western countries in terms of civilisational growth, acceleration of the changes bringing new social phenomena, breaking with the existing social order and trying to transform it profoundly, applying institutional solutions from Western countries in Poland, and a multitude of possible variants of modernisation. As regards the Polish path of modernisation, these authors note, in particular, its imitative character, manifested in the transplantation of political, economic and cultural models drawn from the West. On this account, Polish culture is regarded as an obstacle on the way to modernity. Their assessment of such tendencies is negative since modernisation need not presuppose the rejection of native tradition, as it can become an inseparable component of modernisation.